2022
DOI: 10.1177/25158414211063283
|View full text |Cite
|
Sign up to set email alerts
|

Agreement in anterior segment measurements between swept-source and Scheimpflug-based optical biometries in keratoconic eyes: a pilot study

Abstract: Background: Cataract surgery in keratoconic patients is challenging because of the corneal distortion, which can lead to inaccurate keratometry readings. This study is a comparison of the accuracy of keratometry readings by two types of devices in a tertiary hospital. Purpose: To evaluate the comparability of corneal power measurements, anterior chamber depth (ACD), and white-to-white (WTW) distance between Scheimpflug-based tomography (Pentacam AXL; OCULUS GmbH, Wetzlar, Germany) and swept-source optical biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Previous study had reported that Pentacam had large ACD values than IOLMaster [26]. Besides the difference of measuring mode, the measuring diameters also are different [27][28][29].…”
Section: Discussionmentioning
confidence: 93%
“…Previous study had reported that Pentacam had large ACD values than IOLMaster [26]. Besides the difference of measuring mode, the measuring diameters also are different [27][28][29].…”
Section: Discussionmentioning
confidence: 93%
“…Studies comparing keratometry measurements ( K f , K s , K m , K max ) of Pentacam HR and IOL Master showed no difference in values [27]. By contrast, comparisons of total K of IOLMaster to SimK, TCRP, and TNP of Pentacam AXL revealed that IOL Master results in significantly greater keratometry values and overestimates corneal power [23 ▪ ]. Comparisons of Pentacam HR and Lenstar in keratoconus patients reveal flatter K values with Pentacam [8,25,28].…”
Section: Preoperative Considerationsmentioning
confidence: 88%
“…Pentacam provides multiple measurements of corneal power, including simulated K (SimK), true net power (TNP), equivalent keratometry reading (EKR), and total corneal refractive power (TCRP). Studies comparing these parameters note that TCRP [5,23 ] and TNP [24] measure flatter values compared with SimK, whereas SimK values were significantly greater than EKR at increased corneal zone diameters [25].…”
Section: Preoperative Considerationsmentioning
confidence: 99%
“…Another study showed that IOLMaster measured significantly greater keratometry readings in the steep axis for all participants. The keratometry and WTW measurements of the IOLMaster and Pentacam cannot be used interchangeably in keratoconic patients [ 18 ]. However, it is unclear which measurement mode is most accurate in the surgical planning of toric IOL implantation in eyes with asymmetric bowtie corneal astigmatism.…”
Section: Introductionmentioning
confidence: 99%